Pengaruh Citra Merek dan Harga Terhadap Keputusan Pembelian Hand Sanitizer Dettol di Wilayah Kabupaten Karawng - Mutiara Ramadhani Putri Jangkung; Danny Ramdani (Peneliti.net, 2022)
This study aims to determine the effect of brand image and price on purchasing decisions on Dettol hand sanitizers. This research method is quantitative with descriptive and verification approach. This study uses primary data obtained directly from questionnaires distributed to respondents. The population in this study is unknown, because the exact number of Dettol hand sanitizer users in the Karawang Regency area is unknown. This study uses the formula Hair et al in the calculation of a sample of 140 respondents and is determined by a non-probability sampling technique. The analysis in this study uses path analysis with SPSS 22 software tools. The results of this study indicate that there is an influence between brand image and price on purchasing decisions